Can Identifying and Investigating Fraud Risks Increase Auditors’ Liability? - Reffett, Andrew B. (The Accounting Review, 2010)
ABSTRACT: Legal scholars and accounting practitioners have expressed concern that the U.S. legal system might, in cases of undetected fraud, effectively penalize auditors for identifying and investigating fraud risks (AICPA 2004; Coffee 2004; Golden et al. 2006). This study draws on counterfactual reasoning theory to provide experimental evidence indicating that this concern is warranted. Consistent with counterfactual reasoning theory, I find that evaluators in a natural (i.e., between-participants) environment are more likely to hold auditors liable for failing to detect fraud when the auditors investigated for the perpetrated fraud, relative to when the auditors did not investigate for the fraud. Findings from a less natural within-participants experiment, however, indicate that the between-participant findings likely were unintentional: That is, the same evaluators, when later asked to judge alternative levels of fraud investigation simultaneously, are less likely to hold auditors liable for failing to detect fraud when the auditors investigated for the fraud, relative to when the auditors did not investigate for the fraud.